PENGARUH MOTIVASI, DISIPLIN KERJA, DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN PT SAMOEDRA JAYA GIRI NUSA - I Putu Eka Krisna Santika Wira Anantha; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (VALUES, 2024)
Performance is the result of work that can be achieved by a person or group of people in a company in accordance with the authority and responsibility of each in an effort to achieve organizational goals legally, not against the law and not against morals and ethics. Employee performance is a work result that an employee wants to achieve in a particular job in order to realize a successful job. This study aims to test and obtain empirical evidence on the effect of motivation, work discipline, and workload on the performance of employees of PT Samoedra Jaya Giri Nusa, using a sample of 50 employees. The sampling technique used in this research is saturated sampling technique. Data collection was done through interviews and questionnaires. The data analysis technique used in this research is multiple linear regression analysis which is processed using Statistical Package Social Science (SPSS) version 25. The results showed that motivation, work discipline, and workload had a positive and simultaneous effect on the performance of employees of PT Samoedra Jaya Giri Nusa.